Cellular lipids and protein alteration during biodegradation of expanded polystyrene by mealworm larvae under different feeding conditions. (August 2022) - Tsochatzis, E.D.; Berggreen, I.E.; Vidal, N. Prieto; Roman, L.; Gika, H.; Corredig, M.
Abstract: The present study reports the biodegradation of polystyrene (PS) by mealworm ( Tenebrio molitor ) following different feeding regimes. Changes in lipids and protein were studied to evaluate possible differences in the growth and metabolic pathways of the insects depending on the diets. Thermo-gravimetric analysis of the excretions (frass) revealed a decrease in the molecular mass of the PS polymers. The insects' biomass contained less protein when PS was part of the diet, suggesting that the insects undergo a certain level of stress compared to control diets. The frass also contained lower amount of nitrogen content compared to that from insects fed a control diet. NH4 + and other cations involved in biochemical processes were also measured in insects' frass, including potassium, sodium, magnesium, and calcium, combined with a small pH change. The decrease in the mineral content of the frass was attributed to increased cellular activity in PS-fed insects. A higher amount of ceramides and cardiolipins, biomarkers of apoptosis, were also found in association with PS consumption. It was concluded that the insects could metabolize PS, but this caused an increase in its stress levels. Graphical abstract: Image 1 Highlights: Polystyrene is degraded by Tenebrio molitor larvae. Biodegradation decreases protein biomass. PS -containing diets cause increase in apoptosis biomarkers. There was a decrease in molecular mass of PS. A decrease in mineral content was associated with PS-fed insects.